Evaluation of Student Performance Based on Integrated Teaching Method in Pharmacology Curricula - Zhang, Yulin; Liu, Jia; Xu, Wei; Kong, Qin (Indian Journal of Pharmaceutical Education and Research, 2024)
Aim/Background: The transformation of the “new medical education” model imposes higher demands on universities and educators, representing the latest requirements for the development of medical education. In the past decade, continuous innovations in medicine, pharmaceuticals, and information technology have offered multiple convenient avenues for reform and advancement in medical education. To create “golden courses” that align with the demands of the new medical sciences, we are integrating mobile internet technology with conventional teaching methods to explore various aspects of pharmacology theory and experimental practices. Materials and Methods: A prospective cohort study of medical students enrolled in either conventional or integrated (plus application Moso Tech.) pharmacology curricula. Summative examination performance, job competence, and student self-rating of confidence were compared between the two groups. Results and Discussion: Throughout classroom instruction and practical teaching, over 80% of the students proactively participate in a broad spectrum of pedagogical approaches, resulting in noticeable improvements in their test scores. During the preparatory phase, we gain insights into the specific cognitive areas where students lack proficiency. This information empowers us to prioritize these aspects during instruction for a more targeted teaching approach. Simultaneously, we have received positive feedback, enabling us to enhance our teaching proficiency and student performance more effectively. Most importantly, this diversified teaching approach can augment student’s learning enthusiasm. Various teaching methods can significantly boost students’ comprehensive performance, confidence, and competency in future professional roles. These results highlight the need for potential amalgamation of instructional approaches to enhance the quality of education.
Keywords: New medical construction; Pharmacology education; Integrated teaching method; Medical education; Course reform